What Would Animals Say If We Asked the Right Questions? - Despret, Vinciane (Book collections on Project MUSE., 2016)
Vinciane Despret argues that behaviors we identify as separating humans from animals do not actually properly belong to humans. She does so by exploring incredible and often funny adventures about animals and their involvements with researchers, farmers, zookeepers, handlers, and other human beings. Do animals have a sense of humor? In reading these stories it is evident that they do seem to take perverse pleasure in creating scenarios that unsettle even the greatest of experts, who in turn devise newer and riskier hypotheses that invariably lead them to conclude that animals are not nearly as dumb as previously thought. These deftly translated accounts oblige us, along the way, to engage in both ethology and philosophy. Combining serious scholarship with humor that will resonate with anyone, this book--with a foreword by noted French philosopher, anthropologist, and sociologist of science Bruno Latour--is a must not only for specialists but also for general readers, including dog owners, who will never look at their canine companions the same way again.--COVER.